Tuning the Mechanical and Electrical Properties of Porous Electrodes for Architecting 3D Microsupercapacitors with Batteries‐Level Energy. Issue 15 (20th June 2021) - Li, Congming; Li, Xiangming; Yang, Qingzhen; Sun, Pengcheng; Wu, Lifeng; Nie, Bangbang; Tian, Hongmiao; Wang, Yingche; Wang, Chunhui; Chen, Xiaoliang; Shao, Jinyou
Abstract: Microsupercapacitors (MSCs) are vital power sources for internet of things (IoTs) and miniaturized electronics. The performance of MSCs is often restricted by its low areal energy density, which is due to the low areal mass loading of active materials. Constructing thick planar microelectrode with fine structure and high aspect ratio is an efficient way to increase mass loading, but limited by the breakable nature of porous electrode materials. Here, it is found that the mechanical and electrical properties of porous electrodes, as well as their surface area utilization and internal ion diffusion pathway, can be synergistically tuned by infilling gel electrolyte into internal pores of porous electrode films. The tuned thick porous electrode films are robust enough to enable laser ablation of three dimensional (3D) microelectrodes for high mass loading and high aspect ratio. The areal capacitance of 3D microelectrodes is able to increase linearly with mass loading (or thickness) up to at least 13 mg cm −2  (or 260 µm) for a value of up to 4640 mF cm −2 based on active carbon. The 3D MSCs deliver areal energy density of 1318 μWh cm −2, which is comparable to the best of Li‐ion 3D microbatteries while exhibiting superior electrochemical and mechanical stability. Abstract : The mechanical and electrical properties of thick electrode films are tuned by infilling gel electrolyte, enabling laser ablation of 3D microsupercapacitors (MSCs) with high mass loading and high aspect ratio. The MSCs deliver an energy density of 1318 μWh cm −2, comparable to the best of microbatteries while exhibiting a superior power density of 102 mW cm −2 with high mechanical and cycling stability.